An annotated checklist of the Algerian Cladocera (Crustacea: Branchiopoda) - Ghaouaci, Souad; Amarouayache, Mounia; Sinev, Artem Y.; Korovchinsky, Nikolai M.; Kotov, Alexey A. (Zootaxa, 2018)
We present an annotated checklist of the Cladocera (orders Ctenopoda and Anomopoda) from the continental waters of Algeria, based on published records and original data from analysis of samples from 112 water bodies collected in 2012-2016 in humid and semi-arid regions of the country. Thirty six species have been identified in this study. Three taxa (Daphnia obtusa, D. mediterranea and Ceriodaphnia cf. quadrangula, being an undetermined taxon belonging to the Ceriodaphnia genus) are new to Algeria and eight (Daphnia curvirostris, D. galeata, Macrothrix dadayi, Scapholeberis rammneri, Acroperus angustatus, Ovalona nuragica, O. orellanai and Coronatella anemae) are new to the Maghreb in general. The number of Cladoceran species recorded in Algeria has been raised to 81. More sampling efforts are needed to make this list more complete.